Designing a mobility as a service principled service offering for the minibus taxi industry that improves the user experience—using Stellenbosch as a case study - Mtsi, Thabani Sanda (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.